Nutrition and fertilization management of embryo cultured Makapuno Tall (ECMAKT) seedlings - M. B. Areza-Ubaldo; S. S. Magat; E. P. Rillo; M. I. Secretaria (International Coconut Community Journal, 2005)
A two-year nursery study on ECMAKT coconut seedlings was conducted at the Philippine Coconut Authority - Albay Research Center, Guinobatan, Albay to know the effects of applying different rates of complete fertilizer (14-14-14 fortified with micronutrients) and a foliar fertilizer on the vegetative growth and leaf nutrient status of ECMAKT seedlings. The application of complete NPK fertilizer (14-14-14) at 6-9 g/seedling significantly produced taller seedlings with bigger girth size and more number of living fronds from 2 to 12 months from initial fertilization. The applied rates of complete fertilizer (6-9 g 14-14-14/seedling) on ECMAKT seedlings indicates that the levels of nutrient application (fertilization) is significantly much lower than that of the average rates used in growing ordinary seednuts (seedlings attached to unhusked nuts) in the nursery. The application of foliar fertilizer was ineffective even over the unfertilized ECMAKT seedlings. The better growth of ECMAKT seedlings in terms of their girth, plant height and total living fronds produced were significantly associated with higher levels of leaf K, Cl, and Mn, and lower leaf Na, but with likely adequate leaf P, Mg, S, B, Zn, Cu and Fe based from leaf number 3 (12 month old ECMAKT seedling). The study clearly indicates the necessity of applying inorganic fertilizer i.e. complete fertilizer (14-14-14 fortified with micronutrients) at the moderate rates of 6-9 g/seedling during the nursery stage for proper nutrition and fertilization management to ensure healthy and good quality ECMAKT planting material.